An analysis on the risk premium on wage in the context of the Philippine labor market - Bergante, Blush Paulyn P. (School of Economics, University of the Philippines Diliman, 2018)
With the influx of job opportunities in the Philippines as the economy continues to grow, occupational injuries have also started increasing, which provides an avenue for compensating wage differentials (CWD) in order to attract workers to accept hazardous occupations. A number of related literature have contrasting results regarding this_ some articles say that there is indeed a positive CWD for hazardous occupations (Kneisner and Leet 1991, Kostiuk 1990, Devi, Shanmugam, and Jayasree 2012) and some countries, where unemployment is relatively higher, have negative CWD. This means that workers in hazardous occupations have relatively lower wages than those in non_hazardous occupations (Holmlund 1983, Joyce et. al 2010, Knutsson 2003, Pietroiusti et. al 2010, Schernhammer 2001, Benavides 2000). With such, we use Adam Smith_s CWD theory to look for evidence of hazard premium in highly hazardous occupations in the labor market of Philippines to see if having a highly hazardous occupation really translates to higher wages. Our study uses a wage model to examine the wage differential between highly hazardous and non_hazardous occupations. However, our study shows that in the group of occupations with significant results, we found that, generally, there is actually a negative estimate _ highly hazardous occupations have less wages compared to non-hazardous occupations. This finding is important as it could be a basis for policy intervention since the Philippines has an existing hazard pay scheme for public health workers, and having incentives or compensation for only a specific group of workers with highly hazardous occupation shows unfairness and inconsistency.